ANALISIS INTEGRASI PADI IKAN DALAM PERSPEKTIF AGRO EKONOMI - Atikah Nurhayati (Universitas Muhammadiyah Purwokerto, 2013)
This study aimed to obtain information integration rice fish viewed from the perspective of agroeconomics. This study is motivated by the growth rate of rice production which likely to decline, decline in soil fertility due to continuous intensification. The method used was a survey method by taking the case of rice - fish farming in Solokan Jeruk District Bandung Regency West Java Province. Purposive sampling is used in this research. The expected benefit is to increase rice production, fish seed supply, income and welfare of farmers and the development of efficient utilization of paddy fields. The results showed the integration of fish rice as seen as agro-economic was positively gave the benefit for both farmers and for agricultural land itself. Keywords: rice, agro-economy